PENYALAHGUNAAN NARKOBA DI INDONESIA - Sri Purwatiningsih (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2001)
Drugs abuse has become a crucial problem, since data have indicated that the case increases dramatically. In RSKO (Rehabilitation Hospital for Drugs Addict) the growth of patients in this rehabilitation have increased 400 percent from 1996 to 1999. The increasing of drugs abuse cases predicted to create 'a lost generation' since the most abuser is young generation. Besides, another health problem will follow especially in reproductive health problems. Recently Injecting Drugs Users (IDUs) have been popular practice and they usually exchange syringes and needles. This behavior is a risky factors to transmit the HIV/AIDS. As we know that the transmission of HIV/AIDS through IDU has become the second most after sexual intercourse.Efforts to overcome the problem regarding with drug abuses have not been effectively done. The Indonesian government still behaves in ambiguity to handle drugs abuse problems. To reduce the spread of the HIV/AIDS among IDUs, several institutions offer needle exchange and bleaching programs, in which the government has not been prefered to support them.